(untitled) (Eurasian Research Bulletin, 2022)
This scientific article analyzes the concept of civil society, the stages of its formation and evolution. The social and legal foundations of non-governmental non-profit organizations are disclosed in the framework of reforms for the development of civil society in Uzbekistan.